PENGARUH KINERJA KEUANGAN, GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Fragarian Meydika; Rini Handayani; Sri Lastuti (STIE Atma Bhakti, 2016)
This study aims to prove empirically whether the disclosure of financial performance, GCG, and CSR can increase the value of the company. A total of 30 manufacturing companies listed on the BEI period 2008-2011 serve as samples where sampling is done by purposive sampling method. The data were analyzed using multiple regression with SPSS 17 software. The results showed that financial performance, GCG and CSR had positive effect on firm value. meaning that companies that have good financial performance, implement GCG and CSR in operational activities then the company will increasingly succeed to create value or prosperity for shareholders. Keywords: Financial Performance, GCG, CSR, Corporate Value